PENEGAKAN HUKUM PERSAINGAN USAHA MELALUI PENERAPAN RULE OF REASON PADA KASUS MONOPOLI USAHA - Suryati; Layang Sardana (Justici, 2019)
Article 1 of Law Number 5 Year 2009 concerning Prohibition of Monopolistic Practices and Unfair Business Competition provides a definition of monopoly as "Mastery of production and or marketing of goods and or for the use of certain services by one business actor or a group of business actors". The purpose of this study is to see how enforcement of business competition law through the application of real-reason in the case of monopoly. The method used in this study is normative legal research. The results of this study are generally rule of reason norms in the anti-monopoly law will usually be terminated or contain phrases: (i) which can result in monopolistic practices and / or unfair business competition (ii) which can result in unfair business competition, or (iii) which can result in unfair business competition and / or harm to society.